A SYSTEMATIC LITERATURE REVIEW OF RELATIONSHIP MARKETING FOR SMES A DURING PANDEMIC - Tuti Anggraeni; Dodi Sukmayana; Disman Disman; Puspo Dewi Dirgantar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Relationship marketing (RM) is an important issue in every business because it is a key component of long-term business success. Small and Medium Enterprises (SMEs) are an important business sector in economic growth. This study aims to find out how important RM is for SMEs during a pandemic. This study uses a literature review. Database from Pubmed, ProQuest, Ebsco, and Emerald databases. The keywords used in English are Relationship Marketing, SMEs, and Programs. The data obtained was manually extracted and analyzed descriptively, with the criteria of full text articles, research articles, and the last 10 years of publication period (2013-2022). Found 61 articles related to the research theme, in which RM can help improve the ability of SMEs to gain competitive advantage during the pandemic and discover their strengths and weaknesses to develop critical capabilities for high turbulence and dynamic situations in their environment, and therefore pave the way for improvement towards greater good. Programs that can be carried out to deal with the pandemic are: managing marketing strategies, innovating products, involving the role of the government, and promoting with social media. The results of the study show that RM has an important role in improving the capabilities of SMEs by managing the implementation of marketing strategies in the company.